Development of a nursing assessment form for patients with diabetes mellitus in a hospital: A research and development study - Joeliantina, Anita; Norontoko, Dwi Adji; Anugrahini, Hepta Nur (Belitung Raya Foundation, Indonesia, 2021)
Background: People with Diabetes Mellitus (DM) tend to seek herbal medicine or complementary drugs in their treatments. But, unfortunately, the existing nursing assessment forms have not prepared the format for the use of complementary medicine. Objective: This study aimed to develop a nursing assessment form in patients with DM based on the Chronic Care Model (CCM) approach. Methods: This study employed a Research and Development study design, which consists of ten stages. The nursing assessment form was developed based on CCM theory and integrated complementary medicines into the assessment form. A content validity test was done by four experts and calculated using Aiken's V formula. Face validity among 12 nurses through Focus Group Discussions (FGDs) was also employed to test the quality of the nursing assessment form based on three aspects: functionality, efficiency, and usability. In addition, nine nurses were included for pilot testing of the form. Data were analyzed using descriptive analysis. Results: The nursing assessment form demonstrated a good content validity, with Aiken's V value of 0.94. The form was categorized based on four components of CCM: self-management support, decision support, social activities, and clinical information. Additionally, all nurses could fill the form properly. Conclusion: The nursing assessment form is valid. It can be used for nurses to assess patients with DM based on the CCM with an additional component to evaluate the use of complementary medicine.